1984
DOI: 10.1177/001872678403700601
|View full text |Cite
|
Sign up to set email alerts
|

Spillover from Family to Work: The Neglected Side of the Work-Family Interface

Abstract: It is argued that while researchers have emphasized work's impact on the family, the family exerts important influences on the workplace that have been generally overlooked. This article draws upon evidence of family-to-work spillover from a recent exploratory field study in a large manufacturing plant. Semistructured interviews with 55 employees, both on the job and at home, revealed that most employees recognized that their family lives influenced them at work. Analyses of variance examining positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
321
1
21

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(372 citation statements)
references
References 11 publications
13
321
1
21
Order By: Relevance
“…The inability of the spouse to adjust has been cited in theories and anecdotal studies as a direct and indirect cause of expatriate turnover (e.g., Black 1988; Harvey 1985), and a growing body of empirical evidence supports these influences (e.g., Black and Stephens 1989;Shaffer and Harrison 1998). The spouse's influence on an expatriate's well-being and performance originate from spillover theory which suggests that a working spouse's experiences will carry over into the home and that, likewise, home experiences can influence a person's work life (Aldous 1969;Crouter 1984). Studies by Caligiuri et al (1998) and Takeuchi et al (2002) found spillover effects of spouse on expatriate adjustment and vice versa.…”
Section: Spouse Adjustment and Expatriate Adjustmentmentioning
confidence: 99%
“…The inability of the spouse to adjust has been cited in theories and anecdotal studies as a direct and indirect cause of expatriate turnover (e.g., Black 1988; Harvey 1985), and a growing body of empirical evidence supports these influences (e.g., Black and Stephens 1989;Shaffer and Harrison 1998). The spouse's influence on an expatriate's well-being and performance originate from spillover theory which suggests that a working spouse's experiences will carry over into the home and that, likewise, home experiences can influence a person's work life (Aldous 1969;Crouter 1984). Studies by Caligiuri et al (1998) and Takeuchi et al (2002) found spillover effects of spouse on expatriate adjustment and vice versa.…”
Section: Spouse Adjustment and Expatriate Adjustmentmentioning
confidence: 99%
“…Much of QoL research (e.g., Choi et al, 2007;Diener, 1984;George and Landerman, 1984;Larsen, 1978;Near, 1986;Rahtz and Sirgy, 2000;Rice et al, 1980;Sirgy et al, 2006) has studied vertical spillover effects while a smaller number of studies (e.g., Crouter, 1984;Kremer and Harpaz, 1982;Sirgy et al, 2001;Shepard, 1974) have examined horizontal spillover effects. Further, most research conceptualizes horizontal spillover as a simple one-directional relationship between two life domains in which QoL in a life domain of interest influences QoL in another life domain.…”
Section: Quality Of Life: a Multidimensional Constructmentioning
confidence: 99%
“…Further, most research conceptualizes horizontal spillover as a simple one-directional relationship between two life domains in which QoL in a life domain of interest influences QoL in another life domain. For example, Crouter (1984) studied spillover influence from the family life domain to the work life domain among mothers of young children. Although such a view of horizontal spillover effects may be reasonable for research that has a relatively narrow focus on a few closely related life domains, we believe that it may not depict accurate theorizing about the horizontal spillover process related to IS use in everyday activities.…”
Section: Quality Of Life: a Multidimensional Constructmentioning
confidence: 99%
“…Bu tip çatışmalarda cinsiyet açısından farklılık olduğu ve en fazla erkek çalışanlar açısından bunun yaşandığı görülmüştür. Bu durum bazı araştırmalarla benzer sonuçlar oluşturmaktadır (Crouter, 1984;Duxbury, Higgins, 1991;Gutek, Searle, Klepa, 1991;Duxbury, Higgins, Lee, 1994;Grzywacz, Marks, 2000;Madsen, 2003;Dilworth, 2004;Mennino, Rubin, Brayfield, 2005;Voydanoff, 2005;Cinamon, 2006;Nomaguchi, 2012). Aile ve iş sorumluluğunun ülkemiz gibi toplumlarda daha çok erkek üzerinde toplandığı yönündeki anlayış, bu durumun temel göstergelerinden biri olarak değerlendirilebilir.…”
Section: Sonuçunclassified